Alcohol and Khamr on Fiqh Using Science Experiment Videos in Schools Affected by COVID-19 - Rafika Dwi Rahmah MZ; Suyadi; Zahrul Mufrodi (Universitas Muhammadiyah Sidoarjo, 2021)
Covid-19 has paralyzed Islamic and Natural Science Education in Indonesia. The impact of online learning is not optimal, teachers have difficulty explaining the material or practice making it more difficult for students to understand the material. The purpose of this study was to improve the students' understanding of grade 8 PGRI 6 Denpasar Junior High School on fiqh regarding alcohol and khamr with online learning. The media used is a science experiment video which will have implications for changing the way students perceive the use of alcohol and khamr. This study uses the Nonequivalent Control Group Design method with a comparison between the science experiment class and the control class using the traditional method. The results of the validation of experimental experts, 91.34% fiqh material with perfect criteria. Pretest in the experimental class percentage of 70% sufficient criteria from the experimental class and the control class get a presentation of 72.4% sufficient criteria. Posttest in the experimental class with a percentage of 87.4% good criteria while in the control class presentation 75%.Based on the results of the validation and pretest-posttest comparisons between classes, the experimental method is good for learning fiqh in Islamic education.